PENGARUH INVESTASI DAN INFLASI TERHADAP KESEMPATAN KERJA MELALUI PERTUMBUHAN EKONOMI DI KOTA SAMARINDA - Bayu Dwi Dharma; Sjamsu Djohan (Faculty of Economics and Business Mulawarman University, 2015)
This study has the following objectives: To determine the influence of the Investment and Inflation on Economic Growth in Samarinda To determine the influence of inflation on investment or job opportunities in the city of Samarinda. By using analytical tools such as path analysis, the investment result showed a positive value and significant effect on economic growth in Samarinda. Which means increased investments in Samarinda will boost economic growth significantly. Inflation showed a negative value and significantly influence economic growth in Samarinda. Which means that inflation rates would significantly reduce economic growth. Investments showed a positive value and no significant effect on employment in Samarinda. Which means Increasing Investment in Samarinda not affect the number of jobs significantly. Inflation showed a negative value and no significant effect on employment in the city of Samarinda. Increased inflation does not significantly decrease the employment opportunities in the city of Samarinda. Economic growth showed positive values and do not influence significantly the on employment in the city of Samarinda. The increase did not affect significantly the economic growth of the availability of employment opportunities in the city of Samarinda Keyword: Investment, Inflation, Employment and Economic Growth